Ultrafast spectroscopic characterization and modelling of hybrid plasmonic organic photovoltaic devices - Wu, Bo (2014)
Solar energy is one of the most attractive candidates of alternative energy sources to replace the conventional fossil fuels. Among all kinds of solar cells, polymer-based organic solar cells are one that under spotlight in recent years due to some advantages they possess, e.g., low-cost, solution-processed, properties-tunable, flexible, etc. With the efficiency of organic solar cells exceeding 10%, their shift from lab to factory will materialize soon.